Empathy variation of undergraduate medical students after early clinical contact: a cross-sectional study in China. Issue 7 (19th July 2020) - Ye, Xiong; Guo, Haiying; Xu, Zhou; Xiao, Hui
Abstract : Objectives: Empathy education is very important for medical students. There is little research on the influence of early clinical practice on the development of empathy and other aspects of professionalism in medical students. The aim of this study was to compare the self-reported empathy levels of first-year and second-year undergraduate medical students before and after their early clinical contact curriculum. Setting: The study was conducted at the Shanghai University of Medicine & Health Sciences, Shanghai, China. Participants: A total of 257 undergraduate medical students participated in the study. The 154 first-year students were studying in 10 community-based teaching hospitals, and the 103 second-year students were studying in 3 university-affiliated hospitals. Primary and secondary outcome measures: Primary measures: the Jefferson Scale of Empathy—Student version (JSE-S) was compared between students of different sexes and in different academic years before their early clinical contact course. Secondary measures: comparisons were made after they finished the curriculum 3 weeks later. Results: A total of 219 of 257 students responded (85.21% response rate), and 214 answers could be analysed (135 first-year and 79 second-year students; 120 female and 94 male individuals). No significant differences in the empathy scores before early clinical contact were observed between students of different sexes and in different academic years. After early clinical contact, the mean JSE-S score of the participants was significantly higher than the mean score at the beginning of the curriculum. Conclusions: Empathy-focused training during early clinical contact can improve the empathetic capacity of undergraduate medical students. Fostering empathetic attitudes among undergraduate medical students is necessary for the early stage of their medical education. Further research is needed on the long-term effects of empathy-focused education in entry-level medical students.